Mechanical strain determines the site-specific localization of inflammation and tissue damage in arthritis. Issue 1 (December 2018) - Cambré, Isabelle; Gaublomme, Djoere; Burssens, Arne; Jacques, Peggy; Schryvers, Nadia; Muynck, Amélie; Meuris, Leander; Lambrecht, Stijn; Carter, Shea; Bleser, Pieter; Saeys, Yvan; Hoorebeke, Luc; et al.
Abstract Many pro-inflammatory pathways leading to arthritis have global effects on the immune system rather than only acting locally in joints. The reason behind the regional and patchy distribution of arthritis represents a longstanding paradox. Here we show that biomechanical loading acts as a decisive factor in the transition from systemic autoimmunity to joint inflammation. Distribution of inflammation and erosive disease is confined to mechano-sensitive regions with a unique microanatomy. Curiously, this pathway relies on stromal cells but not adaptive immunity. Mechano-stimulation of mesenchymal cells induces CXCL1 and CCL2 for the recruitment of classical monocytes, which can differentiate into bone-resorbing osteoclasts. Genetic ablation ofCCL2 or pharmacologic targeting of its receptor CCR2 abates mechanically-induced exacerbation of arthritis, indicating that stress-induced chemokine release by mesenchymal cells and chemo-attraction of monocytes determines preferential homing of arthritis to certain hot spots. Thus, mechanical strain controls the site-specific localisation of inflammation and tissue damage in arthritis. Pro-inflammatory factors implicated for the onset of arthritis often have systematic effects, yet arthritis symptoms are mostly limited to the joints. Here the authors show that mechanical strain at the joints promotes the recruitment of monocyte and their differentiation into bone-eroding osteoclast to contribute this tissue specificity.